Promesas y realidades: el fracaso del plan de salida de Estados Unidos de Afganistán (2009-2014) - Baltar Rodríguez, Enrique (El Colegio de México, 2019)
This article aims to demonstrate that the drastic deterioration in Afghanistan’s security situation following the withdrawal of the NATO-led multinational forces in December 2014 has been an inevitable result of the failure of the United States military’s exit strategy. By analyzing a series of indicators related to the levels of violence and insecurity in the country between 2008 and 2014, the author of this article argues that the Obama administration’s military strategy failed to create the conditions for an orderly transfer of responsibilities to the Afghan government within a context of relatively consolidated political stability. As a result, the spiralling violence and insecurity since 2014 continue a trend clearly established in previous years.